192. Tolerability Outcomes of Multi-drug Antibiotic Treatment for Pulmonary Nontuberculous Mycobacterial Disease due to Mycobacterium avium Complex in U.S. Medicare Beneficiaries with Bronchiectasis. (4th December 2021) - Ku, Jennifer; Henkle, Emily; Carlson, Kathleen F; Marino, Miguel; Brode, Sarah K; Marras, Theodore K; Winthrop, Kevin L; Winthrop, Kevin L
Abstract: Background: Nontuberculous mycobacteria (NTM), most frequently Mycobacterium avium complex (MAC), cause increasingly common pulmonary infections. Treatment interruptions and early discontinuation are common in MAC therapy, but population-based data on treatment outcomes are severely lacking. We examined tolerability outcomes of guideline-based 3-drug therapies (GBT) targeted for pulmonary MAC infection. Methods: Among beneficiaries with bronchiectasis (ICD-9-CM 494.0 or 494.1) in U.S. Medicare data (01/2006 – 12/2014), we identified first-time MAC GBT therapy users, excluding those with cystic fibrosis, HIV, or a history of organ transplant. MAC GBT was defined as an overlapping prescription of ≥ 28-day supply of a macrolide, ethambutol and rifamycin. Using Cox regression methods, we compared time-to-regimen change or discontinuation within 12 months of therapy start in the following groups: 1) azithromycin-ethambutol-rifamycin vs. clarithromycin-ethambutol-rifamycin; 2) macrolide-ethambutol-rifampin vs. macrolide-ethambutol-rifabutin; and 3) azithromycin-ethambutol-rifampin vs. clarithromycin-ethambutol-rifabutin. Results: We identified 4, 626 GBT therapy users (mean 77.9 years [s.d. 6.1], female [77.7%], and non-Hispanic white [87.2%]). Overall, the rate of regimen change or discontinuation was higher in the clarithromycin-based regimens compared to azithromycin-containing regimens, and in rifabutin-containing regimens compared to rifampin-containing regimens. The rate of drug regimen change or discontinuation was 65% greater in the clarithromycin-ethambutol-rifabutin group compared to the azithromycin-ethambutol-rifampin group (adjusted hazard ratio: 1.64, 95% CI: 1.43, 1.64) (Table 1, Figure 1 ). Conclusion: Azithromycin-based regimens and rifampin-containing regimens were less likely to be changed or discontinued within 12 months of therapy compared to clarithromycin-based regimens and rifabutin-containing regimens, respectively. More research is needed to identify factors associated with early treatment change or discontinuation. Disclosures: Emily Henkle, PhD, MPH, AN2 (Consultant, Advisor or Review Panel member)Zambon (Advisor or Review Panel member) Theodore K. Marras, MD, Astra Zeneca (Speaker's Bureau)Insmed (Scientific Research Study Investigator)Novartis (Speaker's Bureau)RedHill (Consultant)Spero (Consultant) Kevin L. Winthrop, MD, MPH, Insmed (Consultant, Grant/Research Support)Paratek (Consultant)RedHill (Consultant)Spero (Consultant) Kevin L. Winthrop, MD, MPH, Insmed (Consultant, Research Grant or Support)Paratek (Consultant)RedHill Biopharma (Consultant)Spero (Consultant)